Interpretações e controvérsias nas teorias do éter e do vácuo - Santos, Marcos dos (2015)
Men always have the curiosity of observe natural phenomenon and try to understand it, for simple curiosity or taking advantage of it in his life. From this, he describes his theory to explain the phenomenon, but not all have the same view and due to different influences a lot of controversies are produced about the subject. Some of them are just small discussions and others lead to big revolutions that have an influence on man. This paper is about the importance of the controversies because it stimulates the scientific and philosophical researching that are awaked by the human curiosity, by the expecting knowledge that promotes the science development by rousing searching. A special approach is dedicated to ether theory because not even with the most brilliant minds of the world help a general approval was reached, because even in the 21th century wasn t possible to proof scientifically the existence or not of this important substance to science development